Cultural Production of Adonis as Modern Writer in Arabic Literature Arena - Diah Pramudita; Istadiyantha Istadiyantha; Dwi Susanto (International Journal of Science and Applied Science: Conference Series, 2022)
This study reveal the cultural production of Adonis as a modern writer in Arabic literature arena. Pierre Bourdieu’s theory of cultural production becomes an analytical tool on study. Bourdieu’s theoretical concepts are habitus, capital, practice, trajectories, relations, between objects that support Adonis position as a modern witter. Cultural production of Adonis includes cultural capital in the form of education so that he produces education through literary works, academics, and also Arab cultural scholars. In addition, Adonis is also active in political activities in the Syrian National Socialist Party wich gives him the legitimacy of modern writer in Arena of Arabic Litterature.